PP.20.39: THORACIC AORTA MORPHO-FUNCTIONAL PARAMETERS AND URIC ACID IN MILD NEVER TREATED HYPERTENSIVE PATIENTS. (June 2015) - Moretti, S.; Messina, P.; Maresca, A.M.; Mongiardi, C.; Test, L. Robustelli; Gadaleta, C.; Vacirca, V.; Molaro, M.; Agostinis, M.; Tandurella, N.; Tavecchia, L.; Bertolini, A.; et al.
Abstract : Objective: Uric acid (UA) has a key role in development and progression of hypertension. So we evaluated the relationship between UA and morpho-functional aortic parameters in a cohort of mild hypertensive never-treated patients. Design and method: We enrolled 152 consecutive patients without known cardiovascular diseases, gout or diabetes, not smokers, never treated with antihypertensive drugs and with normal renal function: 88 were hypertensive patients newly diagnosed (BP > 130 and/or 80 mmHg during ABPM), 64 normotensive subjects matched for age, sex and body mass index. All subjects underwent echocardiography to determine aortic parameters (bulb and ascending aorta). They also underwent arterial tonometry to determine central arterial blood pressure, augmentation index (AI) and pulse wave velocity (PWV). Results: UA levels were higher in hypertensive patients (5.3 ± 1.4 vs 4.6 ± 1.2 mg/dL, p 0.003). Renal function was in the normal range and similar in the two groups. Univariate analysis showed a relationship between UA levels and: 24 h SBP (r 0.213, p 0.005), 24 h DBP (r 0.221, p 0.006), aortic bulb diameter (r 0.375, p 0.001), aortic ascending diameter (r 0.232, p 0.004) and AI (r -0.311, p 0.001). No correlations were found between UA and central arterial blood pressure and pulse wave velocity (PWV). Conclusions: In a cohort of mild hypertensive never-treated patients, uric acid levels correlate with 24-hour blood pressure, morphologic aortic parameters and augmentation index. Our results may suggest a role of uric acid in the onset of morphofunctional aortic remodelling. These data need further confirmation from prospective studies.